Frailty and long-term survival of patients with gastric cancer: a meta-analysis - Liang, Hongliang; Hu, Aiping (Frontiers in Oncology, 2023)
The relationship between frailty and the long-term clinical outcome of gastric cancer (GC) patients has not yet been established, although frailty is associated with a poor short-term outcome. The impact of frailty on long-term survival of GC patients was investigated through a systematic review and meta-analysis.Methods: Observational studies with longitudinal follow-ups for a minimum of one year were identified through a search of the PubMed, Embase, Cochrane Library, and Web of Science databases, in accordance with the objective of the meta-analysis.Combining the findings was achieved using a random-effects model, which accounted for inter-study heterogeneity.Results: Ten datasets from nine cohort studies were included, which involved 7613 patients with GC. A total of 2074 patients (27.2%) were with frailty at baseline, and the mean follow-up duration was 48.1 months. A pooled analysis of the results showed that frailty was linked to a poor long-term overall survival in GC patients (risk ratio [RR]: 1.65, 95% confidence interval [CI]: 1.27 to 2.13, p < 0.001; I 2 = 80%). Sensitivity analysis showed consistent results in older patients (≥ 65 years, RR:1.51, p = 0.002) and the oldest old (≥ 80 years, RR: 1.41, p = 0.01). In addition, frailty was also associated with poor long-term progression-free survival (RR: 1.65, 95% CI:1.39 to 1.96, p < 0.001; I 2 = 0%) and disease-specific survival (RR: 1.71, 95% CI:1.23 to 2.37, p = 0.001; I 2 = 4%).Frailty is associated with poor long-term survival of patients with GC.